Randomized Controlled Trial of Strain-Specific Probiotic Formulation (Renadyl) in Dialysis Patients - Natarajan, Ranganathan (Hindawi Publishing Corporation, 2014)
Background. Primary goal of this randomized, double-blind, placebo-controlled crossover study of Renadyl in end-stage renal disease patients was to assess the safety and efficacy of Renadyl measured through improvement in quality of life or reduction in levels of known uremic toxins. Secondary goal was to investigate the effects on several biomarkers of inflammation and oxidative stress. Methods. Two 2-month treatment periods separated by 2-month washout and crossover, with physical examinations, venous blood testing, and quality of life questionnaires completed at each visit. Data were analyzed with SAS V9.2. Results. 22 subjects (79%) completed the study. Observed trends were as follows (none reaching statistical significance): decline in WBC count (−0.51 × 10(9)/L, P = 0.057) and reductions in levels of C-reactive protein (−8.61 mg/L, P = 0.071) and total indoxyl glucuronide (−0.11 mg%, P = 0.058). No statistically significant changes were observed in other uremic toxin levels or measures of QOL. Conclusions. Renadyl appeared to be safe to administer to ESRD patients on hemodialysis. Stability in QOL assessment is an encouraging result for a patient cohort in such advanced stage of kidney disease. Efficacy could not be confirmed definitively, primarily due to small sample size and low statistical power—further studies are warranted.